2023
DOI: 10.1101/2023.02.21.23286227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 preventive measures in Rohingya refugee camps: An assessment of knowledge, attitude and practice toward COVID-19

Abstract: Background: Although many studies were conducted on COVID-19 knowledge, attitude, and practice among the general population in many countries, very little is known about refugees, particularly Rohingya refugees in Cox's Bazar. A vast array of Risk Communication and Community Engagement (RCCE) interventions were implemented in Cox’s Bazar with the intent of reducing disease transmission by empowering the community to adopt public health measures. Objectives: The study aimed to evaluate the current state of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is recognized in some COVID-19 public health guidance that older people, persons with disabilities and/or chronic illnesses face higher risk of COVID-19 and face inequality and barriers to access information, education and services (28). The earlier KAP study found the association between knowledge and practice level and age group, specifically, the older adult age group (≥61 years) had less level of knowledge (AOR 0.42, p = 0.05) (15). This could be explained by the findings of study that the RCCE strategy, messages and the materials were not responsive to the special needs of vulnerable groups, specially, older adult and persons with disability.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…It is recognized in some COVID-19 public health guidance that older people, persons with disabilities and/or chronic illnesses face higher risk of COVID-19 and face inequality and barriers to access information, education and services (28). The earlier KAP study found the association between knowledge and practice level and age group, specifically, the older adult age group (≥61 years) had less level of knowledge (AOR 0.42, p = 0.05) (15). This could be explained by the findings of study that the RCCE strategy, messages and the materials were not responsive to the special needs of vulnerable groups, specially, older adult and persons with disability.…”
Section: Discussionmentioning
confidence: 87%
“…A quantitative KAP study conducted by the same authors prior to this qualitative study found that the majority of the community had a good level of knowledge or awareness on COVID-19 and an average to good level of attitude, however, a significantly low level of practice toward the preventive measures (15). There was a significant improvement in knowledge and attitude among Rohingya refugees compared to the results of previous research (22), however, the practice was not improved as much as the level of knowledge and attitude (15).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations